Analisis Pemanfaatan Kecerdasan Buatan Menggunakan Platform Chat-GPT Untuk Mendukung Proses Pendidikan Bagi Mahasiswa - Rahma Maulida Erizal; Annisa Safitra; Putri Fauzelly Mulia; Zul Azmi (Student Scientific Creativity Journal, 2024)
Intelligence is a system that has been designed using technology to create a computer system that can imitate human intellectual abilities. And it will be possible to interact via text, this chat-gpt definitely has a function, it can translate a language, apart from that, chat-gpt can also provide recommendations, help in the education process, and can also increase productivity. Benefits that will be obtained from chat-gpt GPT in education is learning that is done personally, accessible and affordable, helps students with assignments and can solve problems. But of course, anything created by humans will never be 100% accurate and has no flaws, chat-gpt also has limitations, namely, such as limited understanding, the inability to replace people's creative work, answers that are not always accurate , has an inability to differentiate between a fact and an opinion and the need for a stable internet connection